The Dynamics of the Exchange Rate and Extension of Monetary Trilemma: (Iran Economy Case Study) - Allahyarifard, Mahmoud; Karimzadeh, Mostafa; Falahi, Mohammad Ali; Meidani, Ali Akbar Naji (American Finance & Banking Review, 2020)
Simultaneous making policy of interest rates, exchange rates and capital accounts can be extended to trilemma theory, contrary to its earlier theories, provided that the imbalances of the private sector, the government and the capital account adjusted through the policy variables such as the government expenditures, the interest rates on domestic deposits, the interest rates on domestic loans, effective exchange rates, foreign prices and foreign interest rates. On the other hand, the components of the extension of trilemma theory in the form of internal and external imbalances affect the exchange rate. In other words, if the real sector markets of the economy are not cleared through the aforementioned trilemma components, and policy variables, internal and external imbalances will be affected by opposite direction of net domestic assets (ΔNDA) and net foreign assets (ΔNFA) of the banking system. This is in accordance with the fundamental principles of the monetary approach balance of payments and exchange rate. Policy variables do not put pressure on the unofficial exchange rate as long as they have the same effect on the net changes in the domestic and foreign assets of the banking system. The purpose of this study is to consider the effect of internal and external imbalances on exchange rate through the simultaneous equations system, generating impulses in policy variables, and examining reactions in Iranian economy. In this paper, the monetary exchange rate determination model is analyzed and examined by using the extension of trilemma theory for macroeconomic data of Iran in the form of internal and external imbalances. The results of this study suggest that policy variables can stabilize the unofficial exchange rate (with other conditions being constant) through trading off internal and external imbalances. Thus, the economic policymaker can, while independently policing interest rates, capital accounts and government expenditures and other policy variables in this research, maintain exchange rate stability as a strategic variable and anchor the general level of prices.